1988
DOI: 10.1159/000199615
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Omeprazole Treatment in Man: Effects on Gastric Endocrine Cell Populations

Abstract: 36 patients with chronic gastric or oesophageal peptic ulceration (including 6 with antrectomy), resistant to high-dose ranitidine treatment for at least 3 months, were successfully treated with 40–60 mg of omeprazole daily for periods between 1 and 2 years. Fasting serum gastrin levels were monitored at regular intervals during therapy and multiple gastric mucosal biopsies were taken during gastroscopy every 3–6 months. Gastrin levels increased significantly during the first 6 months of therapy from a medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
1
4

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 15 publications
4
92
1
4
Order By: Relevance
“…The profound reduction in gastric acid secretion induced by PPIs leads to increased secretion of gastrin, and most PPI users have moderate hypergastrinaemia (Lamberts et al, 1988;Klinkenberg-Knol et al, 1994). Gastrin has trophic effects on the gastrointestinal mucosa, and hypergastrinaemia has been associated with an increased risk of gastric carcinoids, and gastric and colonic carcinomas (Havu, 1986;Laine et al, 2000;Gillen and McColl, 2001;Waldum et al, 2005;Kuipers, 2006), although recent results for PPI use and colorectal cancer risk are reassuring (Robertson et al, 2007;Yang et al, 2007;van Soest et al, 2008).…”
mentioning
confidence: 99%
“…The profound reduction in gastric acid secretion induced by PPIs leads to increased secretion of gastrin, and most PPI users have moderate hypergastrinaemia (Lamberts et al, 1988;Klinkenberg-Knol et al, 1994). Gastrin has trophic effects on the gastrointestinal mucosa, and hypergastrinaemia has been associated with an increased risk of gastric carcinoids, and gastric and colonic carcinomas (Havu, 1986;Laine et al, 2000;Gillen and McColl, 2001;Waldum et al, 2005;Kuipers, 2006), although recent results for PPI use and colorectal cancer risk are reassuring (Robertson et al, 2007;Yang et al, 2007;van Soest et al, 2008).…”
mentioning
confidence: 99%
“…Worthy of note here are the results of Creutzfeldt's group [81], who found no densitovolumetric changcs in the oxyntic cell population, even after up to 24 months of 20-60 mg day-', nor any changes in the direction of focal hyperplasia of enterochromaffin-like cells. Gastrin levels in these patients did not exceed the average of 206 pgml-', and rapidly reverted to normal values after drug discontinuation.…”
Section: Proton Pump Inhibitors: Omeprazolementioning
confidence: 57%
“…Finally, many papers have been published concerning the effect of omeprazole administration on the gastric endocrine cells [80][81][82]. Worthy of note here are the results of Creutzfeldt's group [81], who found no densitovolumetric changcs in the oxyntic cell population, even after up to 24 months of 20-60 mg day-', nor any changes in the direction of focal hyperplasia of enterochromaffin-like cells.…”
Section: Proton Pump Inhibitors: Omeprazolementioning
confidence: 88%
“…The PPIs are very efficient drugs in inhibiting gastric acid secretion (67), but at the same time risky due to hypergastrinemia. Rather early, it was shown that PPI treatment induced ECL cell hyperplasia (68), which caused rebound acid hypersecretion (69). A decade later, it was reported that a period of PPI dosed to healthy individuals induced dyspepsia (70) probably due to rebound acid hypersecretion.…”
Section: Gastrin and Gastric Netsmentioning
confidence: 99%